IMPLEMENTATION OF THE PRINCIPLES OF GOOD GOVERNANCE IN IMPROVING PUBLIC SERVICES AT THE INVESTMENT OFFICE AND ONE-STOP INTEGRATED SERVICES OF CENTRAL SULAWESI PROVINCE - Ani Susanti (International Journal Labs, 2022)
Good Governance demands the fulfillment of a number of important indicators. Its realization is only possible through systematic, consistent, and continuous efforts by local governments, legislative institutions, and the community in a synergistic manner. As the implementer, the Regional Government must ensure that the efforts made are in line with the objectives of improving public services as referred to in Law Number 23 of 2014 concerning Regional Government. For this reason, in its implementation, local governments are regularly obliged to compile and report on the performance of the implementation of accountable public services in the principle of regional autonomy, so as to encourage the participation of various elements of the greater community. This research focuses on the implementation of the principles of good governance in the Investment and One-Stop Integrated Services Service (DPMPTSP) of Central Sulawesi Province. The reason is that this office has a strategic role in capital, financing, and cooperation that determines the achievement of regional development goals. The goal is that through this research, it will be known more comprehensively the implementation of good governance in the capital and licensing institutions of the area, especially in the aspects of public services in the field of business licensing for the community. The method used is descriptive qualitative which is analyzed using nine indicators of good governance principles according to the UNDP document (Sedarmayanti, 2010) namely Participation, Rule of Law, Transparency, Responsiveness, Consensus Orientation, Equity, Effectiveness and Efficiency, Accountability, Strategic Vision. The results of the study will be known after the study takes place.